Filosofia e Literatura: distopia como ferramenta de ensino - Sales, Juliana Monteiro da Costa (2025)
In light of the students' great passivity toward theoretical content, which is often seen as tedious, it is always necessary to rethink teaching and learning practices, aiming to, using a term from the philosophy of difference, reterritorialize pedagogical practices, inviting students to fall in love with knowledge. We believe that literature truly has the power to enchant. Through it, we can glimpse fictional worlds, sometimes drawing from the real world, which take us on journeys previously unimaginable. It also makes us return from these fictional worlds and reflect on our own world, on life. Furthermore, the appreciation of literary works as a methodological tool for teaching and learning philosophy can stimulate imagination, intelligence, and critical thinking with regard to reality, while also aiding in the creation of concepts, which, according to Deleuze and Guattari, is what defines philosophy. To this end, this paper explores how the dystopian literature 1984 by George Orwell can be a tool for philosophy classes, serving as a didactic-methodological resource for studying themes such as disciplinary society and society of control alongside readings from thinkers like Michel Foucault, Gilles Deleuze, Félix Guattari, and Ada Kroef. It also discusses the possibility of teaching philosophy as a Concept Factory according to the studies of professor and philosopher Sílvio Gallo. Additionally, it analyzes how dystopian literature is presented or excluded in the book Filosofando by Maria Lúcia de Arruda Aranha and Maria Helena Pires Martins.